The effect of different life experiences on dogs human-directed gazing - Mendes, Juliana Wallner Werneck (2020)
Dogs have been a part of human society for a thousand of years, and we have a particular relationship and communicative interaction, which we discuss in chapter 1. Gazing behaviors are used by dogs to draw a persons attention, indicate the location of a desired object, and initiate communication. In the second chapter of this dissertation, we reviewed the use of the unsolvable task, a common paradigm in studying human-dog communication, discussing how their different methodologies and proxies can affect results and hinder comparisons. We additionally proposed strategies to walk towards a more homogenous use of this important paradigm. In chapter 3 we presented an experiment using the unsolvable task to evaluate the effect of different experiences with humans in dogs gazing behaviors. We compared pet dogs living inside the house, pet dogs living outside the house, and shelter dogs. We found no difference in latency to first gaze, but pet dogs did show a higher proportion of individuals engaging in gaze alternation, a higher number of gaze alternations and a longer duration of gazing than shelter dogs. Additionally, dogs living inside the house gazed more at the experimenter than dogs living outside the house. Overall, our results indicate a strong influence of experience in the development and use of these communicative behaviors in dogs. In chapter 4 we presented an exploratory analyzes of the behavior of shelter dogs in the first solvable trial of the unsolvable task. Fifteen dogs did not obtain food (fail group) and 16 did (success group). Dogs in the fail group had a higher latency to start moving. We presented a time budget for dogs in the fail group. They spent, in average, half of the testing time out of the experimental area and allocated considerable time to walking and sniffing. We discussed these results regarding stress, fear, and the need to explore, and proposed that these are important factors to take into consideration when assessing cognitive abilities in shelter dogs. We additionally discussed strategies to better fit shelter and other non-pet dog populations in current research. Overall, this dissertation brought a new overview, data and discussion contributing to the topic of dog-human communication. This helps us to further understand the process of interspecific communication and of the role of experience in the development of social skills. Finally, but not less important, the understanding of our relationship with dogs can contribute to make the coexistence more harmonious